Healthcare Utilization and Missed Workdays for Parents of Children With Traumatic Brain Injury. Issue 4 (July 2019) - Nelson, Richard E.; Ma, Junjie; Cheng, Yan; Ewing-Cobbs, Linda; Clark, Amy; Keenan, Heather
Abstract : Background: We enrolled patients in a prospective study in which we obtained estimates of the direct and indirect burden for families of children with traumatic brain injury (TBI) relative to a control group of families of children with orthopedic injury (OI). Methods: Parents were surveyed at 3 time points following injury: 3, 6, and 12 months. At each follow-up contact, we asked parents to list the number of workdays missed, number of miles traveled, amount of travel-related costs, and whether their child had an emergency department (ED) visit, hospital admission, any over-the-counter (OTC) medications, and any prescription medications during that time period. We assessed the difference in these outcomes between the TBI and OI groups using multivariable logistic and 2-part regression models to account for high concentrations of zero values. Results: Children with TBI had significantly greater odds of having an ED visit (3.04; 95% CI, 1.12-8.24), OTC medications (1.98; 95% CI, 1.34-2.94), and prescription medications (2.34; 95% CI, 1.19-4.59) than those with OI. In addition, parents of children with TBI missed significantly more days of work (19.91 days; 95% CI, 11.64-28.17) overall during the 12 months following injury than their OI counterparts. Conclusion: Extrapolating our results to the entire country, we estimate that pediatric TBI is associated with more than 670 000 lost workdays annually over the 12 months following injury, which translates into more than 150 million in lost productivity. These missed workdays and lost productivity may be prevented through safety efforts to reduce pediatric TBI. Abstract : Supplemental Digital Content is Available in the Text.